Variations in mechanical properties for different clones of acacia hybrid pulps after beating / Sharmiza Adnan ... [et al.] - Adnan, Sharmiza; Jasmani, Latifah; Saleh, Mahmudin; Mohd Yusoff, Mohd Nor (2004)
Four-and-a-half years old hybrids of Acacia mangium and Acacia auriculaeformis from a thinning exercise were studied for pulp and paper strength. The effects of beating on mechanical strength properties of kraft pulp from locally planted Acacia hybrid clones were investigated. Kraft pulping processes at 12% active alkali were carried out on all clones. The unbleached pulp were beaten at 1000, 3000, 5000 and 7000 revolutions. The mechanical properties of paper produced determined were tear, tensile and burst strengths and folding endurance. The trends after beating and significance of the changes were also compared. It is hoped for that that the findings from this study can be used to determine the suitability of kraft pulps from Acacia hybrid for producing various paper grades.